Smoke bitten - Briggs, Patricia (New York ACE, 2020)
"In this electrifying new entry in the #1 New York Times bestselling urban fantasy series, shapeshifting mechanic Mercy Thompson will face a threat unlike any other. . . . I am Mercedes Athena Thompson Hauptman. My only "superpowers" are that I turn into a thirty-five-pound coyote and I can fix Volkswagens. But I have friends in odd places and a pack of werewolves at my back. It looks like I'm going to need them. Centuries ago, the fae dwelt in Underhill-until she locked her doors against them. They left behind their great castles and troves of magical artifacts. They abandoned their prisoners and their pets. Without the fae to mind them, those creatures who remained behind roamed freely through Underhill, wreaking havoc. Only the deadliest survived. Now one of those prisoners has escaped. It can look like anyone, any creature it chooses. But if it bites you, it controls you. It lives for chaos and destruction. It can make you do anything-even kill the person you love the most. It is here, in the Tri-Cities, in my territory. It won't-can't-remain. Not if I have anything to say about it"--
107868
Keywords: Thompson, Mercy -- (Fictitious character) -- Fiction; Monsters -- Fiction; Werewolves -- Fiction; Shapeshifting -- Fiction; Magic -- Fiction; Fiction / Fantasy / Urban Life; Fiction -- Romance -- Paranormal -- Shifters; Fantasy fiction; Paranormal fiction